Captain Underpants : and the terrifying return of Tippy Tinkletrousers : the ninth epic novel - Pilkey, Dav. (New York : Scholastic, 2012)
After being sent to jail for the rest of their lives, George and Harold are taken on a trip back in time by Tippy Tinkletrousers back to their Kindergarten days where they must deal with their bully without the help of Captain Underpants.
Keywords: Time travel -- Juvenile fiction; Bullying -- Juvenile fiction